Revisiting inclusivity and cultural representation of disability within EFL textbook in Indonesia - Ulya, Muflikhah; Basthomi, Yazid; Febrianti, Yusnita (Abjadia : International Journal of Education, 2025)
Addressing the issues and challenges of inclusivity and disability content in Indonesian EFL textbooks requires a collaborative effort and commitment among textbook authors, publishers, educators, policymakers, and disability advocates to provide equitable learning opportunities for all students. The first step that can be taken to achieve those goals is evaluating the material of the EFL textbook related to inclusivity and disability as curriculum content in Indonesia. Therefore, this research aimed to identify and critically analyze disability as curriculum content in English as a foreign language (EFL) textbooks used in Indonesia. This research was conducted using a qualitative approach that focuses on content analysis. The data sources in this research are three EFL textbooks entitled “English for Nusantara” published by the Ministry of Education, Culture, Research, and Technology of Indonesia and intended for junior high school (VII, VIII, IX grade) students in Indonesia. The findings of this research show that inclusivity and disability-related content are included in the EFL textbook by being represented in images and text. The textbook represents disability in several categories: gender, age, participation, relations, physical activities, and type of disability. Even though the findings show that the textbook "English for Nusantara" has representation for disability, the amount of representation is limited. In conclusion, the research highlights the need for systemic changes in the way disability is represented in educational materials, which could have a profound impact on the inclusivity of educational environments and the broader social integration of people with disabilities.